Fish consumption and risk of contamination by mercury - Considerations on the definition of edible parts based on the case study of European sea bass - Mieiro, C. L.
In the present study, the risk to humans by consuming European sea bass (Dicentrarchus labrax), captured at three sites along a Hg contamination gradient, was evaluated by comparing muscle and kidney total Hg (T-Hg) levels with the European regulations for marketed fish. Moreover, T-Hg and organic Hg (O-Hg) levels in muscle were compared with the Provisional Tolerable Weekly Intake (PTWI) and the Reference Dose (RfD). Although T-Hg levels in muscle were below the European value allowable for marketed fish, kidney’s levels were higher than the set value, stressing the importance of redefining the concept of edible tissue and which tissues should be considered. Mercury weekly ingestion in the contaminated areas was higher than the PTWI, and O-Hg daily ingestion rates were higher than the RfD in all sampling sites. Thus, populations consuming sea bass from the contaminated sites may be at risk, with particular relevance for children and pregnant women.